2014
DOI: 10.2310/7290.2013.00061
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor–Targeted Single-Photon Emission Computed Tomography/Computed Tomography to Detect Activated Macrophages in Atherosclerosis: Can It Distinguish Vulnerable from Stable Atherosclerotic Plaques?

Abstract: The need for noninvasive imaging to distinguish stable from vulnerable atherosclerotic plaques is evident. Activated macrophages play a role in atherosclerosis and express folate receptor folate receptor β (FR-β). The feasibility of folate targeting to detect atherosclerosis was demonstrated in human and mouse plaques, and it was suggested that molecular imaging of FR-β through folate conjugates might be a specific marker for plaque vulnerability. However, these studies did not allow differentiation between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…In humans, 111 In-DTPA-folate and 99m Tc-EC20-folate have been tested in clinical trials as radiotracers for imaging of cancer (FR-a) (29,30). Nevertheless, Winkel et al showed that 111 In-EC0800 (a radiolabeled folate compound) detects plaque but was not able to differentiate between a stable and a vulnerable atherosclerotic carotid plaque in a shear stress-induced ApoE KO mouse model (31). However, in this model macrophage content is not different between the oscillatory shear stress region (stable plaque) and the lowered shear stress region (vulnerable plaque) (32).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, 111 In-DTPA-folate and 99m Tc-EC20-folate have been tested in clinical trials as radiotracers for imaging of cancer (FR-a) (29,30). Nevertheless, Winkel et al showed that 111 In-EC0800 (a radiolabeled folate compound) detects plaque but was not able to differentiate between a stable and a vulnerable atherosclerotic carotid plaque in a shear stress-induced ApoE KO mouse model (31). However, in this model macrophage content is not different between the oscillatory shear stress region (stable plaque) and the lowered shear stress region (vulnerable plaque) (32).…”
Section: Discussionmentioning
confidence: 99%
“…The result is a weak fibrous cap that is highly susceptible to rupture. 8,24 Thus, a real need to develop a noninvasive molecular imaging tool for early differentiation of stable and vulnerable atherosclerotic plaques is evident.…”
Section: Discussionmentioning
confidence: 99%
“…8 Vulnerable plaques possess a thin fibrous cap over a large fatty core and inflammatory cells (eg, MΦ) within the plaque that release enzymes (such as collagenases 23 ) at the same time, breaking down collagen in the cap. The result is a weak fibrous cap that is highly susceptible to rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clinical study showed that 99m Tc-etarfolatide imaging may be more sensitive than physical examination for assessing disease activity in rheumatoid arthritis patients (33). Other FRimaging agents have potential to visualize macrophage activation in osteoarthritis and atherosclerosis (34,35 …”
Section: Potential Future Application Of 99m Tc-etarfolatide Imagingmentioning
confidence: 99%